Correction of professional burnout of health workers in the process of mindfulness-based training - K. M. Popova; M. Yu. Kuzmin (Acta Biomedica Scientifica, 2024)
Background. The article reviews the problem of testing the in-person version of the burnout reduction program "OsNOVA" for health workers.The aim of the work. To present the results of the program immediately after its completion and to study the sustainability of the effect.Materials and methods. As part of the program testing, 49 doctors and nurses were interviewed. The following methods were used: Maslach Burnout Inventory; Lazarus and Folkman Inventory of Coping Strategies; Beck Depression Inventory; Perceived Stress Scale 10; Short Form 12 questionnaire; mindfulness questionnaires.Results. It was found that when implementing a program to reduce the level of professional burnout in medical workers, held in-person, there is a statistically significant decrease in those subjects whose burnout was initially high. This is accompanied by an increase in mindfulness (primarily such components as Non-judgmentalism, Observation and Awareness of Actions), productive coping strategies. Health workers with a relatively low level of burnout had an improvement in a number of indicators reflecting the burnout level, as well as an increase in the quality of life. The effect achieved by the program persisted for at least three months after the end of its active part.Conclusion. The "OsNOVA" program in an in-person format can be used to prevent professional burnout of health workers. Additional work is planned for its further improvement.